Funny Lady - Herbert Ross; Vereen, Ben, 1946-; Carole Wells; James Caan; Larry Gates; Omar Sharif; Roddy McDowall; Barbra Streisand (USA Columbia Pictures Corporation, 1975)
1930s in New York. The famous singer Fanny Brice has divorced her first husband Nicky Arnstein. During the depression she has trouble finding work as an artist but meets Billy Rose, a newcomer who writes lyrics and owns his own nightclub.
Story of singer Fanny Brice's stormy relationship with showman Billy Rose.
Arnold Schulman
Languages: English, German, French, Spanish, Italian Subtitles: English, French, Turkish, Arabic, Portuguese
Keywords: Comedy; Drama; Romance; Musical